2016
DOI: 10.1159/000442813
|View full text |Cite
|
Sign up to set email alerts
|

The Real-World Routine Use of Caffeine Citrate in Preterm Infants: A European Postauthorization Safety Study

Abstract: Background: Caffeine citrate is the treatment of choice for apnea of prematurity (AOP). Regulatory agencies have requested real-world data on drug utilization and safety, a postauthorization safety study, of a pharmaceutical-grade caffeine citrate, Peyona®, to confirm its benefit for preterm infants. Objectives: To investigate the clinical use, outcomes, and safety profile of this pharmaceutical-grade caffeine citrate in the routine treatment of preterm infants with a gestational age (GA) <37 weeks. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…A recent cross-sectional survey of neonatologists in Thailand, Lebanon, Australia, and the US revealed that prophylactic use of methyxanthines for apnea of prematurity is common, with 62% of those surveyed reporting prophylactic use 17 . Similarly, caffeine was used for apnea prophylaxis in 37% of preterm infants in a mulitcenter prospective study in Austria, Czech Republic, Greece, Italy, and Spain 18 .…”
Section: Effect Of Caffeine On Respiratory Outcomes In Preterm Infantsmentioning
confidence: 99%
“…A recent cross-sectional survey of neonatologists in Thailand, Lebanon, Australia, and the US revealed that prophylactic use of methyxanthines for apnea of prematurity is common, with 62% of those surveyed reporting prophylactic use 17 . Similarly, caffeine was used for apnea prophylaxis in 37% of preterm infants in a mulitcenter prospective study in Austria, Czech Republic, Greece, Italy, and Spain 18 .…”
Section: Effect Of Caffeine On Respiratory Outcomes In Preterm Infantsmentioning
confidence: 99%
“…The methylxanthine caffeine is commonly used to reduce apnea of prematurity [39, 40]. Of note, caffeine treatment has been associated with reduced incidences of BPD [41] and the prevention of hyperoxia-mediated pulmonary inflammation and lung injury [42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…The latest Cochrane review in 2010 [38] did not support routine use of prophylactic caffeine, but a series of recent retrospective studies have shown that early administration of caffeine (in the first 48 h of life) significantly reduced length of MV and improved short-term respiratory outcomes in preterm infants [39,40]. As a result, the off-label use of prophylactic caffeine has risen from 22% (at the time of the CAP trial) to 60-75% [39,41,42]. The first dose is given anytime between days 1 to 25 of life and for a duration ranging from 2 to 119 days [42].…”
Section: Adjuvant Therapiesmentioning
confidence: 99%
“…As a result, the off-label use of prophylactic caffeine has risen from 22% (at the time of the CAP trial) to 60-75% [39,41,42]. The first dose is given anytime between days 1 to 25 of life and for a duration ranging from 2 to 119 days [42]. There are also noticeable differences in practices related to monitoring and discontinuation of caffeine.…”
Section: Adjuvant Therapiesmentioning
confidence: 99%